Konsep Fisika Perpindahan Panas dalam Kearifan Lokal Miyang Tuban - Muthi'ah, Lathifatul; Admoko, Setyo; Krisanti, Galuh Dwi; Mahfudloh, Durriyah Amirotul; Damarsha, Adrian Bagas (Experiment: Journal of Science Education, 2025)
Physics learning faces serious challenges as students perceive physics as a complex subject that is difficult to implement in daily life. This research aims to explore the local wisdom of fishermen in "Miyang" (fishing) activities in Tuban as a context for ethnoscience-based physics learning and Socio-Scientific Issues (SSI) approach on heat transfer concepts. The research method uses a qualitative approach with observation, interview, documentation, and literature study techniques. The research subjects are fishermen who carry out Miyang activities in the coastal areas of Tuban Regency. Data were analyzed using qualitative descriptive analysis through data reduction, triangulation, comparative analysis, description-interpretation, and conclusion drawing. The research results show that Tuban fishermen have accurate understanding of land breeze and sea breeze phenomena that align with the concept of heat transfer by convection. Fishermen utilize land breeze for journeys to the open sea at night and sea breeze for return trips during the day, demonstrating efficient utilization of natural energy. This traditional knowledge represents an example of indigenous knowledge that can be integrated into ethnoscience-based physics learning, providing authentic learning contexts that help students understand that physics concepts are integrated into daily life. This research successfully identified land breeze and sea breeze phenomena as complex Socio-Scientific Issues that combine scientific aspects with social dimensions. In conclusion, the local wisdom of Tuban fishermen has a strong scientific foundation and great potential as a source of contextual and meaningful ethnoscience-based physics learning.